2019
DOI: 10.1108/jidob-04-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual disabilities and offending behaviour: the awareness and concerns of the police, district attorneys and judges

Abstract: Purpose -The purpose of this paper is to examine the awareness of intellectual disabilities (ID) amongst professionals in the criminal justice system (CJS) and their knowledge of those persons, either as victims, witnesses, suspects, accused or defendants. Design/methodology/approach -A survey of the professionals in the CJS (n ¼ 388), combined with a series of focus group interviews with experienced professionals (n ¼ 20), was conducted. Findings -One out of three respondents (police, district attorneys and j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Her former viewpoint may be explained by the criminal justice system giving more attention to offenders than victims. This may also be re ected in the research (29), where the criminal justice system reported twice the number of alleged offenders with intellectual disabilities compared to victims with the same diagnosis.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Her former viewpoint may be explained by the criminal justice system giving more attention to offenders than victims. This may also be re ected in the research (29), where the criminal justice system reported twice the number of alleged offenders with intellectual disabilities compared to victims with the same diagnosis.…”
Section: Discussionmentioning
confidence: 90%
“…Another Norwegian study looking at cases investigated by the police found that 71.2 % of victims with intellectual disabilities were females and that 30 % of these cases led to a penal sanction (28). A study by Søndenaa, Olsen (29) found that the criminal justice system respondents observed intellectual disability twice as often in suspects compared with victims. The study results (29) showed that all professional parties (police, state attorneys and jurors) reported more frequent contact with suspects with intellectual disabilities than with victims or witnesses with the same diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another Norwegian study looking at cases investigated by the police found that 71.2% of victims with intellectual disabilities were females and that 30% of these cases led to a penal sanction [ 34 ]. A study by Søndenaa, Olsen [ 35 ] concluded that intellectual disability was detected twice as often in suspects compared with victims in the criminal justice system. The study results showed that all professional parties (police, state attorneys and jurors) reported more frequent contact with suspects with intellectual disabilities than with victims or witnesses with intellectual disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…The study results showed that all professional parties (police, state attorneys and jurors) reported more frequent contact with suspects with intellectual disabilities than with victims or witnesses with intellectual disabilities. These results may be explained by the fact that the criminal justice system has more contact with suspects of sexual assault with intellectual disabilities, than victims with intellectual disabilities [ 35 ].…”
Section: Introductionmentioning
confidence: 99%